Synthesis and evaluation of isatin derivatives as effective SARS coronavirus 3CL protease inhibitors - Chen, Li-Rung (Bioorg Med Chem Lett, 2005)
N-Substituted isatin derivatives were prepared from the reaction of isatin and various bromides via two steps. Bioactivity assay results (in vitro tests) demonstrated that some of these compounds are potent and selective inhibitors against SARS coronavirus 3CL protease with IC(50) values ranging from 0.95 to 17.50 μM. Additionally, isatin 4o exhibited more potent inhibition for SARS coronavirus protease than for other proteases including papain, chymotrypsin, and trypsin.